Electrical power unit commitment : deterministic and two-stage stochastic programming models and algorithms /: deterministic and two-stage stochastic programming models and algorithms. (2017) - Huang, Yuping; Pardalos, P. M (Panos M.), 1954-; Zheng, Qipeng P
No abstract available